Molecular studies reveal a speciation process within Ryvardenia cretacea (Polyporales, Basidiomycota) - Rajchenberg, Mario (2012)
rDNA sequentiation and phylogenetic analysis of the ITS region of strains of the brown-rot polypore Ryvardenia cretacea from Australia (Tasmania, Victoria) and Argentina (Patagonia) revealed the existence of two well supported clades. Each clade appears restricted to one side of the Pacific indicating a strong biogeographical isolation between strains and populations in the process of speciation. Nevertheless, detailed studies and comparisons did not show the existence of significant morphological differences. This fact, coupled with previously reported dikaryon x monosporic mating tests which showed biological compatibility between specimens from both regions, supports the maintenance of a complex but taxonomically single entity.